Performance Analysis of User Speed Impact on IEEE 802.11ah Standard affected by Doppler Effect - Marwan, Abdul Aziz; Perdana, Doan; Sanjoyo, Danu Dwi (International journal of communication networks and information security, 2018)
Internet of Things (IOT) offers a new dimension of technology and information where connectivity is available anywhere, anytime, and for any purpose. IEEE 802.11 Wireless Local Area Network group is a standard that developed to answer the needs of wireless communication technology (WI-Fi). Recently, IEEE 802.11 working group released the 802.11ah technology or Wi-Fi HaLow as a Wi-fi standard. This standard works on the 1 GHz frequency band with a broader coverage area, massive device and the energy efficiency issues. This research addresses, the influence of Doppler Effect using Random Waypoint mobility model on 802.11ah with different user speed are analyzed. The design of the simulation system is done by changing user speed and MCS. Based on the result, it can be concluded that the overall performance of the network with all of the parameter scenarios is decreasing along with the increasing user speed, RAW group, and bandwidth. In the user speed scenario, the MCS 5 with RAW group = 2 and bandwidth = 2 MHz in v = 10 km/h scenario has the worst performance with an average delay which is about 0.065463 s, average throughput is about 0.328120 Mbps, and average PDR is about 99.8901%.